Agentic and Communal Social Motives. Issue 10 (5th October 2015) - Locke, Kenneth D.
Abstract People chart and navigate their social lives along two cardinal axes – agency and communion. The motives to approach communion (e.g., enhance closeness and cooperation), approach agency (e.g., gain status and control), avoid communion (e.g., limit vulnerabilities and obligations), and avoid agency (e.g., limit resentments and rivalries) can each be adaptive, depending on the person and situation. After reviewing common implicit and explicit measures of agentic and communal motives, I describe how these motives together shape (and are shaped by) diverse phenomena, such as individuals' involvements in mating and parenting and, concurrently, their testosterone and oxytocin levels. I also detail how normative models of development and maturation depict a shifting dynamic between communal and agentic motives over the lifespan: In childhood, secure attachments provide foundations for developing agency; in adulthood, the challenge becomes yoking agency (one's accumulated mental, physical, and social resources) to communal aims (nurturing others and prosocial endeavors).